The effect of commercial feeds with different protein content on the growth and survival of tiger shrimp fry (Penaeus monodon) - Sihombing, Andri; Febri, Suri Purnama; Isma, Muhammad Fauzan; Haser, Teuku Fadlon; Nazlia, Suraiya; Aprita, Ika Rezvani; Rusydi, Rachmawaty; Nurdin, Muh Saleh (Universitas Malikussaleh, 2023)
In Aceh Province, tiger prawns (Penaeus monodon) are one of the main commodities of farmers for cultivation. Feed is one of the factors that can support the development of tiger prawn culture. The quality feed is feed that contains essential nutrients in sufficient quantities, one of which is protein. This study aims to determine the effect of commercial feed with different protein content on the growth and survival of tiger prawn fry. This study used a completely randomized design (CRD) method consisting of 3 treatments and 4 repetitions, namely P1 (using 40% protein feed), P2 (using 35% protein feed), and P3 (using 26% protein feed). The results showed that commercial feed with different protein content had an effect on active weight growth and feed conversion ratio, but had no effect on tiger prawn survival. Furthermore, the best protein content for the growth and survival of tiger prawn was obtained, namely 40%.Keywords: commercial feed; growth; protein; survival rate; tiger prawn.